2009
DOI: 10.1152/japplphysiol.91453.2008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of adaptations in aerobic capacity and submaximal energy metabolism provides a unique insight into determinants of human aerobic performance

Abstract: It has not been established which physiological processes contribute to endurance training-related changes (Delta) in aerobic performance. For example, the relationship between intramuscular metabolic responses at the intensity used during training and improved human functional capacity has not been examined in a longitudinal study. In the present study we hypothesized that improvements in aerobic capacity (Vo(2max)) and metabolic control would combine equally to explain enhanced aerobic performance. Twenty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
138
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 53 publications
24
138
0
3
Order By: Relevance
“…Of particular interest, citrate synthase maximal activity in soleus muscle positively correlated with running performance (r ϭ 0.46, P Ͻ 0.05), whereas the correlation between left ventricular contractile function and running performance was not significant (r ϭ 0.22, P Ͼ 0.12). It is clear that these findings do not guarantee a causal relationship between skeletal muscle aerobic capacity and running performance in our model, but they corroborate previous reports from the literature, demonstrating a strong correlation between skeletal muscle parameters and functional capacity in patients with HF (24) and important relationships between metabolic skeletal muscle adaptations and training and improvements in performance (56). An increased percentage of type I (i.e., oxidative) fibers in soleus and plantaris muscles of both trained groups is further evidence that CMT and HIT enhanced skeletal muscle aerobic metabolism in infarcted rats.…”
Section: Discussionsupporting
confidence: 64%
“…Of particular interest, citrate synthase maximal activity in soleus muscle positively correlated with running performance (r ϭ 0.46, P Ͻ 0.05), whereas the correlation between left ventricular contractile function and running performance was not significant (r ϭ 0.22, P Ͼ 0.12). It is clear that these findings do not guarantee a causal relationship between skeletal muscle aerobic capacity and running performance in our model, but they corroborate previous reports from the literature, demonstrating a strong correlation between skeletal muscle parameters and functional capacity in patients with HF (24) and important relationships between metabolic skeletal muscle adaptations and training and improvements in performance (56). An increased percentage of type I (i.e., oxidative) fibers in soleus and plantaris muscles of both trained groups is further evidence that CMT and HIT enhanced skeletal muscle aerobic metabolism in infarcted rats.…”
Section: Discussionsupporting
confidence: 64%
“…Alternatively, it could be that our small sample included several non-responders. Previous studies have comprehensively demonstrated that following a period of exercise training part of the population will not adapt for specific parameters (non-responders), and for insulin sensitivity this has been shown to be the case for up to 40% of the population (Boule et al 2005;Vollaard et al 2009;Bouchard and Rankinen 2001). Therefore, further studies with larger sample sizes will be needed to confirm or refute our initial observations.…”
Section: Discussionmentioning
confidence: 67%
“…These adaptations include hemodynamic, metabolic, and cardiovascular adaptations, such as CH. CH is a physiological increase in left ventricle (LV) mass that contributes to increased ventricular stroke volume and cardiac output (32,38).This CH phenotype is associated with sarcomeres added in series to lengthen the cardiac cell, as well as in parallel. In contrast to pathological CH, physiological CH induced by aerobic training occurs in response to intermittent volume…”
mentioning
confidence: 99%
“…These adaptations include hemodynamic, metabolic, and cardiovascular adaptations, such as CH. CH is a physiological increase in left ventricle (LV) mass that contributes to increased ventricular stroke volume and cardiac output (32,38).…”
mentioning
confidence: 99%